Effect of Binder Types and Its Concentrations on Sausage Formulations from Asian Green Mussel and Tempeh Flour - Anugerah Dany Priyanto; Sri Djajati (Jurnal Ilmu Pangan dan Hasil Pertanian, 2020)
Asian green mussels are fishery products found in both traditional and modern markets, but the characteristics of fresh products are rapidly decreasing in physical and chemical quality. Processed product is one option to extend the shelf life and one of product is made into sausage due to its heating process can kill microorganisms. The purpose of this study is to improve consistency of texture that will affect organoleptic characteristics by adding variations of hydrocolloid types with different concentrations. The Completely Randomized Design (CRD) was used as the design of experiment with hydrocolloid type variables, such as alginate, carrageenan, and CMC with 3 variations of concentrations specifically 1%, 2%, and 3%. The results of this study had a significant influence on the physical and chemical properties of sausages (P <0.05). Sausage from Asian green mussels and tempeh flour with the addition of 2% CMC was chosen as the best formulation because it has the highest level of preference from sensory evaluation. Some physical properties of these sausages include texture 120.11 ± 16.5 mm/g.s, water holding capacity (WHC) 52.43 ± 0.04%, and emulsion stability 73.23 ± 0.37%. In addition, the chemical characteristics of this sausage are water content of 52.50 ± 0.09%, ash content of 2.49 ± 0.26%, protein content of 19.94 ± 0.35%, and fat content of 12.72 ± 0.56%. Hopefully, the development of this product can be one of the strategies in utilizing Asian green mussels in extending their shelf life.